Analysis of flour market segments: a study of how specialty products affect volume, sales dollars, and margin dollars - Garr, Andrew Lee (Kansas State University, 2017)
The objectives of this thesis is to use regression models and market trends to determine whether the changing product mix of Ardent Mills has an impact on volume, sales dollars, and margin dollars. The results will be used to build a market analysis of Ardent Mills’ product mix strategy. Flour milling is a highly competitive industry. Ardent Mills is constantly looking to increase profits and become more valuable to its customers. Specialty products have created a new opportunity, but the opportunity costs must also be considered. Determining what new products to develop, where to manufacture them, and whether to create new capacity or convert existing capacity are difficult decisions that must be made. The data used in this thesis were collected from Ardent Mills’ sales records from June 1, 2014 through December 31, 2016. Type of product, sales volume, sales dollars, and margin dollars were collected for each month to be analyzed. The study determined that increasing the volume of whole wheat flour sales decreases white flour volume, total flour volume, white flour sales dollars, and total flour sales dollars. Increasing the volume of UltraGrain increases white flour sales dollars and total flour sales dollars. Increasing the volume of wheat-based specialty products increases the volume of white flour and the volume of total flour. As the demand for UltraGrain and wheat-based specialty products increases, the demand for white flour increases as well. Decreasing wheat prices have allowed for additional margin to be captured.
Keywords: Milling; Flour; Wheat; Specialty products; Whole wheat flour; Ultragrain